'Effects of' and 'effects with' captions: How exactly does watching a TV programme with same-language subtitles make a difference to language learners?. (1st July 2013) - Vanderplank, Robert
Abstract : Ever since Karen Price's ground-breaking work in 1983, we have known that same-language subtitles (captions) primarily intended for the deaf and hearing-impaired can provide access to foreign language films and TV programmes which would otherwise be virtually incomprehensible to non-native-speaker viewers. Since then, researchers have steadily built up our knowledge of how learners may make use of these when watching. The question remains, however, whether, and to what extent, watching subtitled programmes over time helps develop learners' language skills in various ways. Perhaps surprisingly, this question of long-term language development has still not been fully addressed in the research literature and we appear to be in a largely 'confirmatory' cycle. At an informal level, on the other hand, there are countless stories of learners who have been assisted in learning a foreign language by watching subtitled or captioned films and television. I shall review the contributions of key research studies to build up a picture of the current state of our knowledge and go on to outline, first, the current gaps in research and, second, some encouraging new approaches to learning by autonomous 'users' of foreign-language Internet media and same-language subtitles across languages, now more widely available.